Redundant unbalance compensation of an active magnetic bearing system. (15th September 2017) - Hutterer, Markus; Kalteis, Gerald; Schrödl, Manfred
Highlights: Unbalance control can be used without a communication between the motor controller and the magnetic bearing controller. Two redundant selfsensing strategies are combined for estimation the angular velocity and the angle of the rotor. The unbalance vibration can be significantly reduced using the proposed selfsensing approaches. The proposed selfsensing unbalance control is tested on an industrial magnetic bearing system. Abstract: To achieve a good running behavior of a magnetic levitated rotor, a well-developed position controller and different compensation methods are required. Two very important structures in this context are the reduction of the gyroscopic effect and the unbalance vibration. Both structures have in common that they need the angular velocity information for calculation. For industrial applications this information is normally provided by an angle sensor which is fixed on the rotor. The angle information is also necessary for the field oriented control of the electrical drive. The main drawback of external position sensors are the case of a breakdown or an error of the motor controller. Therefore, the magnetic bearing can get unstable, because no angular velocity information is provided. To overcome this problem the presented paper describes the development of a selfsensing unbalance rejection in combination with a selfsensing speed control of the motor controller. Selfsensing means in this context that no angle sensor is required for the unbalance or torque control. With such structures two redundant speed and angle information sources are available and can be used for the magnetic bearing and the motor controller without the usage of an angle sensor.